Acute toxicity of the aqueous extract of Aloe barbadensis miller gel - Abderrahmane, F; Addou, S; Labadie, I; Kheroua, O (Bangladesh Journal of Scientific and Industrial Research, 2023)
Aloe vera (A v) is a medicinal plant used since ancient times. Itsmucilage contains no less than 75 active ingredients with multiple properties. The present research aims to study the acute toxicity of the aqueous extract of A v gel (AEAVG) and to determine itsno-toxic effect dose (NTED). After the aqueous extraction of A v gel, an acute toxicity study was conducted in Swiss mice for 14 days by oral administration of AEAVG in a single dose (0, 250, 500, and 1000 mg/kg BW). Acute toxicity evaluation affected mouse behavior, weight gain, food and water intake, serum biochemical parameters (transaminases, urea, and albumin), and organ histology (liver and kidneys). These results show that the NTED is lower than 500 mg/kg BW. AEAVG has toxic effects at doses equal to or greater than 500 mg/kg BW, raising the alarm about the therapeutic use of AEAVG. Bangladesh J. Sci. Ind. Res. 58(1), 19-34, 2023